MEDIA BRANDING IN JAVANESE LOCAL MEDIA “PANJEBAR SEMANGAT” - Ratih Pandu Mustikasari; Oktifani Winarti; Hanna Nurhaqiqi (Universitas Islam Balitar, 2021)
The digital era is exposing the media industry and the audience to a new phenomenon, it is convergence. Convergence becomes a real challenge have to be faced by the entire media industry, from global to local media industries. The convergence faced by local media is a bigger challenge due to limited financial and resources. Various studies show that adaptation is mostly done by utilizing platforms in new media to re-embrace segmentation and even add new audience segmentations. The forms of adaptation presented show the elements of branding media in it. According to Malmelin and Moisander (2014) there are five concepts of branding media that are often used, they are brand extension, brand as identity, brand as differentiation, brand as equity, and brand as a product. This article will show the side of branding media by the local Javanese language magazine